Back squat depth influences activation of some, but not all lower limb muscles in collegiate American football players - Atkins, L. T.; Huckaby, T.; Nicks, K.; Parker, A.; Roberson, J.; Denney, T.; Schultz, J. (Isokinetics and Exercise Science, 2025)
Background It is unclear how back squat depth influences muscle activation and should be considered when designing strength training programs. Current evidence suggests this relationship is population-specific and should be examined in different populations to optimize strength training outcomes. This study examined the effect of different squat depths on muscle activation in college football players.